1991
DOI: 10.1093/ajcn/54.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid and apolipoprotein concentrations in healthy men on diets enriched in either canola oil or safflower oil

Abstract: This randomized, blind study measured changes in serum lipid and apolipoprotein concentrations in 16 men consuming 39 +/- 1% of energy (en%) as fat either from safflower- or canola-oil-based diets for 8 wk. Initially, the men were stabilized for 3 wk on a typical American (baseline) diet. Compared with baseline, the vegetable-oil-based diets reduced serum total cholesterol 9-15% (P less than 0.002), low-density-lipoprotein (LDL)-cholesterol 12-20% (P less than 0.002), and apolipoprotein B-100 21-24% (P less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 22 publications
2
27
2
Order By: Relevance
“…Effects on serum lipids, lipoproteins, and apolipoproteins are in line with earlier intervention studies with rapeseed oil (McDonald et al, 1989;Wardlaw et al, 1991;Valsta et al, 1992;Nydahl et al, 1994). Even with the relatively high fat content of the test diets, we found lower total and LDL cholesterol levels, apo B concentrations, and LDL=HDL ratios and no differences in HDL cholesterol levels after the RO diet compared to the SAT diet.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Effects on serum lipids, lipoproteins, and apolipoproteins are in line with earlier intervention studies with rapeseed oil (McDonald et al, 1989;Wardlaw et al, 1991;Valsta et al, 1992;Nydahl et al, 1994). Even with the relatively high fat content of the test diets, we found lower total and LDL cholesterol levels, apo B concentrations, and LDL=HDL ratios and no differences in HDL cholesterol levels after the RO diet compared to the SAT diet.…”
Section: Discussionsupporting
confidence: 85%
“…This development may lead to an increased dietary intake of MUFAs and PUFAs, especially a-linolenic acid (18:3 n-3). Several intervention studies with rapeseed oil-rich diets have shown favourable effects on the blood lipid profile in healthy volunteers (McDonald et al, 1989;Wardlaw et al, 1991;Valsta et al, 1992;Nydahl et al, 1994) and in hyperlipidemic patients (Lichtenstein et al, 1993;Gustafsson et al, 1994;Nydahl et al, 1995). In these studies, serum levels of total and low-density lipoprotein (LDL) cholesterol were reduced, while serum levels of triglycerides and highdensity lipoprotein (HDL) cholesterol remained unchanged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…. , 27)ondiet</(<2=l 65) with the composition of that particular diet was modeled as follows: 33 Grundy et aP 4 Katan et al 35 McDonald et al 36 Mensink and Katan 10 Ginsberg et al 37 Mensink and Katan 38 Wardlaw and Snook 39 Berry et al 40 Chan et al 41 Wardlaw et al 42 VaJsta et al 43 Sat, saturated fatty acids; mono, monounsaturated fatty acids; poly, polyunsaturated fatty acids. ' x, Rotating-diet, crossover, or Latin square design; //, parallel design.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the economic aspect, in Brazil, safflower oil has a higher commercial value than soybean oil since the former is an imported product. Some studies have shown the beneficial effects of PUFA of safflower oil on energy metabolism and its contribution to reducing body fat (WARDLAW et al, 1991). However, these results can also be observed with the intake of other polyunsaturated oils such as soybean oil (RAMADAN et al, 2009; RUIZ-RODRIGUEZ; REGLERO; IBAÑEZ, 2010).…”
Section: Resultsmentioning
confidence: 99%